The Role of Interpersonal Communication in First-born Female Generation Z as a Sandwich Generation in Medan Sunggal - Salim, Desi Ayu Fitria; Sikumbang, Ahmad Tamrin (Ilomata International Journal of Social Science, 2025)
This study aims to explore the subjective experiences of first-born daughters of Generation Z who play the role of the sandwich generation in multigenerational family structures. Using a descriptive qualitative approach, this study delves into the deeper meanings of the dual roles played by the respondents through in-depth interviews, non-participatory observation, and documentation. The study involved five participants selected using purposive sampling, with criteria including being the first-born daughter aged between 21 and 26 years, residing in Medan Sunggal District, and actively involved in meeting the emotional and economic needs of their families. Data analysis was conducted thematically using the Miles and Huberman model, validated through triangulation, member checking, and academic discussion. The results of the study indicate that first-born daughters face structural, emotional, and cultural pressures that demand adaptive resilience. Open, empathetic, and equal interpersonal communication is the primary tool for negotiating expectations and maintaining psychological stability within the family. The three theories used interpersonal communication, role burden, and family system are able to explain the complexity of power relations and responsibilities within the family. These three concepts are interconnected in shaping the dynamics of the dual roles performed by the informants, where communication serves as the primary mechanism for managing role burdens within the demanding family system structure. These findings emphasize that dual roles are not merely practical but also emotional, making them crucial figures in maintaining family balance. This study recommends support from families, communities, and educational institutions in creating safe and dialogic spaces for first-born daughters so that their roles can be more psychosocially sustainable.